1993
DOI: 10.1016/0735-1097(93)90190-c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on valvular resistance in patients with mitral stenosis

Abstract: In patients with mitral stenosis, the exercise-induced changes in valvular resistance are heterogeneous. This is the result of the variable response of mitral valve area to an increase in flow. In the individual patient, mitral valve area can significantly increase, a factor that has to be taken into account when interpreting the hemodynamic relevance of the obstruction. Calculated valvular resistance is flow dependent and has no advantage over valve area calculations for quantifying mitral stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…Our study found that the mean transmitral pressure gradient increased significantly from baseline to peak in both groups, Voelker et al . and Grimaldi et al .…”
Section: Discussionsupporting
confidence: 70%
“…Our study found that the mean transmitral pressure gradient increased significantly from baseline to peak in both groups, Voelker et al . and Grimaldi et al .…”
Section: Discussionsupporting
confidence: 70%
“…First, the increase in TMG during exercise is more attenuated in RMA patients than in patients with similar resting hemodynamics but with a more fixed orifice, as seen in organic mitral stenosis (30,31) and mechanical MVR (32). When describing and grading the degree of functional stenosis after RMA on the basis of resting data alone, it is important to realize the possible dynamic behavior of the EOA, especially in patients with beneficial LV remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…However, exercise wedge pressure, resting MVA, and gradients do not strictly correlate with exercise capacity and symptoms due to flow dependence properties of the mitral valve and PAP estimations [6,7,[19][20][21]. It is already recognized that exercise Doppler can help to refine the judgment about the hemodynamic severity of the MS [6,8,22].…”
Section: Hemodynamic Implications Of Impaired Right Ventricular Contrmentioning
confidence: 91%